LA SAISIE ÉMOTIVE DU « KAIROS » AVEC DES ENFANTS : ENTRE ACTE PHILOSOPHIQUE ET GESTE DIDACTIQUE - Claire POLO; Kristine LUND (Studia Universitatis Babeș-Bolyai. Philosophia, 2021)
Emotional Grasping of the Kairos in Children’s Talk: between Philosophical Act and Didactical Gesture. An essential gesture of animating a philosophical dialogue with children consists in grasping within their talk, an opportune word or turn of phrase, the kairos, and bouncing off it to advance reasoning. Based on the analysis of expert practices, we propose a typology of the emotional grasp of Kairos that reflects the tension between investigative and educational aims in these exchanges. Beyond the effect of surprise, regulation makes it possible to welcome and share one's emotions and to make them evolve into wonder, astonishment or doubt. Such trajectories are decisive for the future of the new idea. But other reactions are frequent, offering other opportunities for the current activity and children training in the long term.